Intravenous Dexmedetomidine Versus Paracetamol for Postoperative Pain Relief in Laparoscopic Surgery: A Comparative Study - Sarkar, Manjula; Desai, Pushkar; Pawaskar, Shantaram; Sarkar, Shubhra (New Frontiers in Medicine and Medical Research Vol. 7, 2021)
Background: Acute pain in the perioperative setting is detrimental to post operative outcome and adequate analgesia leads to better outcome. It increases sympathetic response of the body with subsequent rise in oxygen consumption of body, risk of deep vein thrombosis due to immobility and consequent pulmonary embolism. Methods: Sixty ASA I/II patients between 18- 65 years undergoing laparoscopic cholecystectomy and appendicectomy were included and randomly divided into 2 groups. ASA III/IV patients, previous opioid and alpha 2 agonist treatment and patients requiring extensive surgical dissection were excluded. Group D received IV Dexmedetomidine 1 \(μ\)g/kg over 10 min followed by 0.2-0.7 \(μ\)g /kg/hr and Group P received IV Paracetamol 15 mg/kg prior to extubation. Patients were monitored for hemodynamics and VAS score was assessed after extubation till 24 hours. Rescue analgesia (IV tramadol 1 mg/kg) was given and the time interval till the requirement of first dose of rescue analgesia was recorded. Results: In group D, 12 patients required rescue analgesia as compared to 4 Patients in group P (40% vs13.3%; P=0.02). VAS scores were similar in both groups with group P showing trend towards low score. Median time at which the first dose of rescue analgesia was administered in group P was longer (134.42 + 12.67 vs 82.76 + 9.38 min; P=0.001). Incidence of bradycardia and hypotension was higher in group D (20% vs 3.3%; P=0.04). Conclusion: Paracetamol is a superior to Dexmedetomidine for analgesia in short surgical procedures and should form a part of multimodal analgesia.